The Katyn massacre 1940 : history of a crime - Urban, Thomas (2020)
Zusammenfassung: In the spring of 1940, Stalin's NKVD executed 22,000 Polish officers, ensigns and state officials near the Russian village of Katyn and other places. When Wehrmacht soldiers discovered some of the graves three years later, the Soviets succeeded in convincing US President Roosevelt of the German perpetration. British Prime Minister Winston Churchill had no clear picture of the crime, and therefore made no public comments. Using thousands of recently released US documents, this book refutes the popular thesis that the Western Allies deliberately lied about the Katyn case in order not to endanger the alliance with Stalin. Completely new for research is the role that Hitler's opponents in the Wehrmacht played in solving the crime: at the Nuremberg trial they convinced the US delegation that the executors were not from the SS, but from the NKVD.